THE ROLE OF A NOTARY IN TRANSFERRING TITLE TO LAND THAT DOES NOT HAVE TITLE (NOT CERTIFIED) (Study at the Notary/PPAT Office: PERAN NOTARIS DALAM PERALIHAN HAK ATAS TANAH YANG BELUM MEMILIKI HAK (BELUM BERSERTIFIKAT) (Studi di Kantor Notaris/PPAT - Lestari, Endang (LPPM UPMI, 2023)
In the case of taking legal action to transfer a right to land or building, it can usually be done by way of buying and selling, grants, exchange, separation and division of inheritance and so on. The transfer of land rights by buying and selling that do not have rights (not yet certified) is carried out by relinquishing land rights with compensation made before a notary so that the strength of proof is perfect.This type of research uses empirical legal research using an empirical juridical research approach and a sociological approach, the data used in this study are primary data as the main data obtained directly from interviews and secondary data as supporting materials obtained from legal materials. Based on the results of the research, the researchers concluded that the role of the notary in the transfer of land rights that have not been certified in Medan City, especially in Deli Serdang Regency, Patumbak District, which is located in Hamlet VI (six) Patumbak Kampung Village, is to make an authentic deed of relinquishment of land rights that has been determined by law, guaranteeing the certainty of the date of the making of the deed, providing grosse, and besides that the notary also plays an important role in providing legal advice, explanations and instructions to the parties facing the things that can be done or prohibited related to applicable laws and regulations. As well as correcting typographical errors or typos contained in the signed minutes of deed.